Questions & Answers

Question

Answers

$

\left( {3k + 1} \right)x + 3y - 2 = 0 \\

\left( {{k^2} + 1} \right)x + \left( {k - 2} \right)y - 5 = 0 \\

$

Answer
Verified

Hint: Convert the equations into matrix format and Equate the determinant $D$ of this matrix to zero using this to calculate the value of k to reach the answer.

Complete step-by-step answer:

Given system of equations is:

$

\left( {3k + 1} \right)x + 3y - 2 = 0 \\

\left( {{k^2} + 1} \right)x + \left( {k - 2} \right)y - 5 = 0 \\

$

Convert these equations into matrix format

$ \Rightarrow \left[ {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right]\left[ {\begin{array}{*{20}{c}}

x \\

y

\end{array}} \right] = \left[ {\begin{array}{*{20}{c}}

2 \\

5

\end{array}} \right]$

The system of equations has no solutions if the value of determinant $\left( D \right) = 0$, and at least one of the determinant $\left( {{D_1}{\text{ and }}{{\text{D}}_2}} \right)$ is non-zero.

So, determinant $\left( D \right)$ of the above system of equations is given below

So, ${\text{D = }}\left| {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right|$

Now put this determinant equal to zero and calculate the value of $k$ for which the system of equations has no solution.

$

\Rightarrow {\text{D = }}\left| {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right| = 0 \\

\Rightarrow \left( {3k + 1} \right)\left( {k - 2} \right) - \left( {{k^2} + 1} \right)3 = 0 \\

\Rightarrow 3{k^2} - 6k + k - 2 - 3{k^2} - 3 = 0 \\

\Rightarrow - 5k - 5 = 0 \\

\Rightarrow k = - 1 \\

$

So, for $k = - 1$, the value of determinant is zero.

Now calculate the value of determinant ${{\text{D}}_1}$ at this value of $k$, to ensure that the condition is satisfied for no solution. The value of determinant ${{\text{D}}_1}$ should not be equal to zero.

If first column is replaced with column $\left[ {\begin{array}{*{20}{c}}

2 \\

5

\end{array}} \right]{\text{ }}$, then the determinant D is converted into determinant ${{\text{D}}_1}$, according to Cramer Rule.

$ \Rightarrow {{\text{D}}_1} = \left| {\begin{array}{*{20}{c}}

2&3 \\

5&{\left( {k - 2} \right)}

\end{array}} \right| = \left| {\begin{array}{*{20}{c}}

2&3 \\

5&{\left( { - 1 - 2} \right)}

\end{array}} \right| = 2\left( { - 1 - 2} \right) - 3 \times 5 = - 6 - 15 = - 21 \ne 0$

Therefore the system of equations has no solution for $ k = - 1$.

Note: Whenever we face such types of questions the key concept we have to remember is that put determinant ${\text{D = 0}}$, then calculate the value of $k$, then at this value of $k$ if the value of determinant ${{\text{D}}_1}{\text{ or }}{{\text{D}}_2}$ is non-zero then the system of equations has no solution at this value of $k$.

Complete step-by-step answer:

Given system of equations is:

$

\left( {3k + 1} \right)x + 3y - 2 = 0 \\

\left( {{k^2} + 1} \right)x + \left( {k - 2} \right)y - 5 = 0 \\

$

Convert these equations into matrix format

$ \Rightarrow \left[ {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right]\left[ {\begin{array}{*{20}{c}}

x \\

y

\end{array}} \right] = \left[ {\begin{array}{*{20}{c}}

2 \\

5

\end{array}} \right]$

The system of equations has no solutions if the value of determinant $\left( D \right) = 0$, and at least one of the determinant $\left( {{D_1}{\text{ and }}{{\text{D}}_2}} \right)$ is non-zero.

So, determinant $\left( D \right)$ of the above system of equations is given below

So, ${\text{D = }}\left| {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right|$

Now put this determinant equal to zero and calculate the value of $k$ for which the system of equations has no solution.

$

\Rightarrow {\text{D = }}\left| {\begin{array}{*{20}{c}}

{\left( {3k + 1} \right)}&3 \\

{\left( {{k^2} + 1} \right)}&{\left( {k - 2} \right)}

\end{array}} \right| = 0 \\

\Rightarrow \left( {3k + 1} \right)\left( {k - 2} \right) - \left( {{k^2} + 1} \right)3 = 0 \\

\Rightarrow 3{k^2} - 6k + k - 2 - 3{k^2} - 3 = 0 \\

\Rightarrow - 5k - 5 = 0 \\

\Rightarrow k = - 1 \\

$

So, for $k = - 1$, the value of determinant is zero.

Now calculate the value of determinant ${{\text{D}}_1}$ at this value of $k$, to ensure that the condition is satisfied for no solution. The value of determinant ${{\text{D}}_1}$ should not be equal to zero.

If first column is replaced with column $\left[ {\begin{array}{*{20}{c}}

2 \\

5

\end{array}} \right]{\text{ }}$, then the determinant D is converted into determinant ${{\text{D}}_1}$, according to Cramer Rule.

$ \Rightarrow {{\text{D}}_1} = \left| {\begin{array}{*{20}{c}}

2&3 \\

5&{\left( {k - 2} \right)}

\end{array}} \right| = \left| {\begin{array}{*{20}{c}}

2&3 \\

5&{\left( { - 1 - 2} \right)}

\end{array}} \right| = 2\left( { - 1 - 2} \right) - 3 \times 5 = - 6 - 15 = - 21 \ne 0$

Therefore the system of equations has no solution for $ k = - 1$.

Note: Whenever we face such types of questions the key concept we have to remember is that put determinant ${\text{D = 0}}$, then calculate the value of $k$, then at this value of $k$ if the value of determinant ${{\text{D}}_1}{\text{ or }}{{\text{D}}_2}$ is non-zero then the system of equations has no solution at this value of $k$.

×

Sorry!, This page is not available for now to bookmark.